The effect of intrapartum maternal fever on neonatal outcomes: a systematic review and meta-analysis - Ling, Qian; Wan, Haixia (Frontiers in Pediatrics, 2025)
ObjectiveTo systematically review the link between intrapartum maternal fever and adverse neonatal outcomes in term singleton pregnancies not complicated by chorioamnionitis.MethodsThe PubMed, Web of Science, Scopus, and Embase databases were searched for studies published up to June 30, 2024, that reported data on women with term singleton pregnancies and intrapartum fever. Studies describing cases of chorioamnionitis (CAM) were excluded. The included studies had to have defined exclusion criteria to ensure that women with a high likelihood of CAM were excluded. Neonatal outcomes of interest were infection/sepsis, fetal distress, assisted ventilation, low APGAR scores, neonatal intensive care unit (NICU) admission, seizures, and hypotonia. Study quality was assessed by the Newcastle-Ottawa Scale (NOS). A random-effects model was used to pool effect sizes, which were reported as odds ratios (OR) and weighted mean differences (WMD). Funnel plots and Egger's test were used to assess publication bias.ResultsA total of 11 studies (n = 153,410) were included. Neonates born to mothers with intrapartum fever had a higher risk of low APGAR scores (OR 2.97, 95% CI: 1.61, 5.48), need for assisted ventilation (OR 2.50, 95% CI: 1.59, 3.93), infection/sepsis (OR 6.01, 95% CI: 2.68, 13.5), NICU admission (OR 2.77, 95% CI: 1.40, 5.51), seizures (OR 4.25, 95% CI: 1.95, 9.22), and hypotonia (OR 4.19, 95% CI: 1.72, 10.2). The birth weight of neonates delivered by febrile mothers was significantly higher (WMD 63.4 g, 95% CI: 16.2, 110.5). Publication bias was noted for low APGAR scores and neonatal infection/sepsis.ConclusionIntrapartum maternal fever appears to be associated with increased risks of adverse neonatal outcomes. However, the challenge of entirely excluding CAM-related fever and variability in study methodologies limits the robustness of the findings. Nonetheless, proactive management of maternal fever during labor could be critical.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024565830, PROSPERO CRD42024565830.